Treatment of Acidified Blood Using Reduced Osmolarity Mixed-Base Solutions - Mason, Thomas G.; Kraut, Jeffrey A. (Frontiers in Physiology, 2016)
We hypothesize that reduced osmolarity mixed-base (ROMB) solutions can potentially serve as customizable treatments for acidoses, going beyond standard solutions in clinical use, such as 1.0 M sodium bicarbonate. Through in silico quantitative modeling, by treating acidified canine blood using ROMB solutions, and by performing blood-gas and optical microscopy measurements in vitro, we demonstrate that ROMB solutions having a high proportion of a strong base, such as disodium carbonate or sodium hydroxide, can be effective in reducing carbon dioxide pressure PCO2 while raising pH and bicarbonate ion concentration without causing significant osmotic damage to red blood cells, which can occur during rapid administration of hypertonic solutions of weak bases. These results suggest that a ROMB solution, which is composed mostly of a strong base, could be administered in a safe and effective manner, when compared to a hypertonic solution of sodium bicarbonate. Because of the reduced osmolarity and the customizable content of strong base in ROMB solutions, this approach differs from prior approaches involving hypertonic solutions that only considered a single molar ratio of strong to weak base. Our calculations and measurements suggest that custom-tailored ROMB solutions merit consideration as potentially efficacious treatments for specific types of acidosis, particularly acute metabolic acidosis and acute respiratory acidosis.